Jabatan Gerejawi: Kajian Biblis 1 Timotius 3:1-7 Terhadap Kualitas Pemimpin Kristen - Alon Mandimpu Nainggolan; Elisabet Hia (Pascasarjana IAKN Manado, 2021)
This article is a literary study with a biblical study which suggests the concept of an ecclesiastical office based on 1 Timothy 3: 1-7 on the quality of Christian leaders. To describe this, the author presents various information from primary and secondary sources related to the research topic which is then presented descriptively. From the research carried out, the concept of the quality of Christian leaders based on 1 Timothy 3: 1-7 is important to be understood and demonstrated by Christian leaders today in order to be able to address various challenges in the midst of his leadership. There are five qualities that must be possessed by a Christian leader, among others; spiritual quality, personality quality, cognitive quality, social quality and professional quality. One factor that makes Christian leaders ineffective, efficient and productive in their leadership practices is due to lack of understanding and living the quality of Christian leaders based on the Bible, specifically 1 Timothy 3: 1-7.